The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jmii.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Severe macrolide-resistant Mycoplasma pneumoniae pneumonia associated with macrolide failure

Abstract: We investigated differences in outcomes between 68 children hospitalized with macrolide-sensitive Mycoplasma pneumoniae pneumonia (MSMP group) and 25 children hospitalized with macrolide-resistant M. pneumoniae pneumonia (MRMP group). In the MRMP group, 19 children received macrolides and clinical failure occurred in six of which five had pneumonia progression during therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 10 publications
3
32
2
Order By: Relevance
“…Although previous data from patients with MRMP pneumonia suggest that the presence of resistance did not increase the overall severity of disease, recent reports have demonstrated that disease progression during therapy, with increased complications, occurred in patients with MRMP pneumonia 2021. Surveillance data from Japan have also shown that cases requiring hospitalization have gradually increased as MRMP pneumonia in children increased 8.…”
Section: Discussionmentioning
confidence: 91%
“…Although previous data from patients with MRMP pneumonia suggest that the presence of resistance did not increase the overall severity of disease, recent reports have demonstrated that disease progression during therapy, with increased complications, occurred in patients with MRMP pneumonia 2021. Surveillance data from Japan have also shown that cases requiring hospitalization have gradually increased as MRMP pneumonia in children increased 8.…”
Section: Discussionmentioning
confidence: 91%
“…This retrospective study was conducted in a health care region in Hong Kong comprising one university-affiliated hospital with 1,600 beds, three extended-care hospitals with a total of 1,600 beds, and one pediatric hospital with 160 beds. A diagnostic PCR assay for M. pneumoniae was provided as a routine service for inpatients by a clinical microbiology laboratory (7,16). Testing was initiated by clinicians, mainly in patients with features suspected to be due to M. pneumoniae pneumonia (2,17).…”
Section: Methodsmentioning
confidence: 99%
“…In nine patients, no information on the syndromic diagnosis was available. Clinical features and macrolide resistance genotyping results for 101 of the patients were reported previously (7,16). Nucleic acid extracts from the 257 patients with positive M. pneumoniae results were retrospectively retrieved for further testing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, macrolide resistance of M. pneumoniae, which is acquired by mutations of the ribosomal target of macrolides,11 has been spreading rapidly and widely since 2000,12 resulting in enhanced disease severity with increased complications 13, 14…”
Section: Introductionmentioning
confidence: 99%